Lumber Herniated Disc Presenting with Incomplete Cauda Equina Syndrome - İş, Merih; GEZEN, Ferruh; KARATAŞ, Ayşe; YILDIZ, Hakan (Cerrahpaşa Medical Journal, 2014)
Herniated lumbar discs presenting with cauda equina syndrome are rare. This is a case report of a patient with lumbar herniated disc presenting with partial cauda equina syndrome. The patient applied to our department with perianal hypoesthesia and sphincter disfunction without motor deficit and sciatica. Santral disc herniation was determined on level of L5-S1 and patient was operated. Cauda equina syndrome needs urgent diagnosis and surgical treatment. The patients may apply with just some of the symptoms of the cauda equina syndrome as our patient.